GCSE Higher mathematics - Hony, B. V. (Longman, 2002)
This highly motivating course has been written to match the requirements of the Higher Tier for all GCSE specifications. The course comprises a Students' Book and Answer Book for each year, with ICT activities and weblinks contained on the fully integrated website.